Filipino and Korean students' schema and reading comprehension of folk narratives in English - Moratilla, Noel Christian A. (2009)
The purpose of this study was to establish the relationship between cultural/referential background, also known as scheme, and the reading comprehension of folk narratives in English. Fifteen Korean and 15 Filipino graduating high school students were selected for the study. They were asked to read two folk narratives, one from the Philippines and the other from Korea, both of which were written in English. The mean of the grades of the students were compared and analyzed. Results showed that the participants scored higher in retelling narratives from the country of their origin. Retelling of a text of the reader's own culture showed easy recall of details, more effective sense of engagement with the text and construction of generalizatios and summaries. When the text reflects another culture, the retelling contains awkward syntax and fails to include culture-specific items in relation to the other country.